2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6347307
|View full text |Cite
|
Sign up to set email alerts
|

X-ray simulation with the Monte Carlo code PENELOPE. Application to Quality Control

Abstract: A realistic knowledge of the energy spectrum is very important in Quality Control (QC) of X-ray tubes in order to reduce dose to patients. However, due to the implicit difficulties to measure the X-ray spectrum accurately, it is not normally obtained in routine QC. Instead, some parameters are measured and/or calculated. PENELOPE and MCNP5 codes, based on the Monte Carlo method, can be used as complementary tools to verify parameters measured in QC. These codes allow estimating Bremsstrahlung and characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…It has been pointed out in the literature that modifications of the transport parameters C1 and C2 for high‐energy electrons in the target, even with small nonzero values, may affect water dosimetry . However, there is no evidence indicating that the use of VRIF may bias simulations in water . In our opinion, the most efficient strategy is to develop an EFEN by fixing the transport parameters only after the use of some VRT over the target.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been pointed out in the literature that modifications of the transport parameters C1 and C2 for high‐energy electrons in the target, even with small nonzero values, may affect water dosimetry . However, there is no evidence indicating that the use of VRIF may bias simulations in water . In our opinion, the most efficient strategy is to develop an EFEN by fixing the transport parameters only after the use of some VRT over the target.…”
Section: Discussionmentioning
confidence: 93%
“…Unlike other authors, we found a deterioration in the simulation efficiency with the use of C1 and C2 parameters in combination with VRIF F = 150 (see Fig. ).…”
Section: Discussionmentioning
confidence: 99%
“…The simulation tools that are most commonly used today are Monte Carlo simulations (e.g. EGS, MCNP, Fluka, Penelope and GEANT (Bielajew et al 1994, Baró et al 1995, Agostinelli et al 2003, Ferrari et al 2005, Allison et al 2006, Reed 2007, Ljungberg and King 2012, Pozuelo et al 2012). The models range from pure mathematical models (ICRP 1979, Zankl et al 1988) to various anthropomorphic voxel phantoms (Zubal et al 1994, Xu et al 2000, Petoussi-Henss et al 2002, Kramer et al 2004, Lee et al 2006, Menzel et al 2009, Xu and Eckerman 2010.…”
Section: Computation Of Dosementioning
confidence: 99%
“…Muitas aplicações são encontradas na literatura utilizando o PENELOPE, com destaque para metrologia, mamografia, radiologia diagnóstica, entre outros. Bastante utilizado desde geometrias simples às mais complexas, como forma de estimar o comportamento de determinado sistema a ser estudado [22][23][24]. Este algoritmo de simulação pode ser aplicado para modelagens com energias iniciais entre 1 keV e 1 GeV.…”
Section: Penelopeunclassified